Pengaruh Arus Kas Bebas, Profitabilitas, dan Ukuran Perusahaan Terhadap Kebijakan Utang - Rizanti, Puti Zhafira; Gurendrawati, Etty; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The Effect of Free Cash Flow, Profitability, and Company Size on Debt Policy in LQ45 Companies Listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. This research was conducted to determine the effect of free cash flow, profitability, and company size on debt policy. This research uses LQ45 companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period as the population. This research method uses quantitative methods with data in the form of financila reports available IDX website. The sample was selected using purposive sampling and produced 108 observation data. The data were processed using the SPSS application and analyzed using multiple linear regression analysis. Based on the results of the analysis conducted, it can be concluded that profitability does not have a significant effect on debt policy. Meanwhile, free cash flow and company size have a significant effect on debt policy.